PERBEDAAN EFEKTIVITAS METODE CERAMAH DENGAN METODE PEER EDUCATION TERHADAP PENGETAHUAN REMAJA TENTANG HIV/AIDS TAHUN 2013 - Komang Suryaningsih (Coping: Community of Publishing in Nursing, 2014)
Number of people infected with HIV/AIDS in Bali continues to increase. In August 2012 since 1987, cases of HIV/AIDS were recorded in Bali reached 6,504 cases, Denpasar city was ranked first by the number of cases in 2611. In Bali, about 130 adolescent aged 15-19 tested positive for HIV/AIDS until August 2012. Health education will be very useful to improve the knowledge of adolescents about HIV/AIDS when applied through appropriate methods. This study aimed to determine differences in effectiveness of the lecture methods with peer education methods on adolescent knowledge about HIV/AIDS at SMKN 3 and SMKN 4 Denpasar. This study is a quasi experimental study (nonequivalent control group design). The sample consisted of 40 adolescents were selected by quota sampling, divided into two groups: control and experimental groups. The control group is lecture methods and the experimental group is peer education methods. The data was collected using a questionnaire with multiple choice type questions. The results are mean-average knowledge after treatment in lectures group is 74.30 and 79.50 in peer education group. Based on t test this difference was statistically significant with a significance level of p=0.003 (p <0.05) that means there are differences in the effectiveness of the lecture methods with peer education methods on adolescent knowledge about HIV/AIDS in 2013 at SMKN 3 and SMKN 4 Denpasar. Based on the results of this study are expected that peer education methods can be a new methods in health education that effective to increase adolescent knowledge about HIV/AIDS either by health workers, teachers and KPA.